The changes of serum prostate specific antigen level in advanced prostate cancer patients undergoing palliative transurethral prostate resection - Kurniawan, Wikan; Hardi, Hidayu Permata (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Total Prostate specific antigen (tPSA) is a substance secreted by the prostate gland. It levels vary depending on the condition of the prostate and typically increase in response to increased prostate volume, cancer, infection, urinary retention and others. Conversely, tPSA levels decrease following a reduction in prostate volume. Palliative transurethral resection of the prostate (pTURP) is a procedure performed to relieve urinary retention in patients with metastatic prostate cancer who are not candidates for, or do not consent to, definitive treatment.Objective: This study aims to compare tPSA levels before and after pTURP in patients with advanced prostate cancer.Method: Using retrospective cross-sectional studyutilized patient medical records and laboratory results to compare pre- and post-operative tPSA levels. Data were collected from the UGM Academic Hospital's medical record between 2019 and 2022. Inclusion criteria included patients with available pre-operativeand post-operative tPSA levels and anatomic pathology results. Tumor characteristics were classified as cT3-4 or cN+ with any PSA level and any ISUP grade. Patients presented with symptoms such as urinary obstruction, pelvic pain, and/or haematuria, and all diagnoses were confirmed via prostate biopsy. Data were analyzed using the Mann-Whitney U test.Results: A total of 40 patients met the inclusion criteria. The mean average age was 72.45 years. The average resection time was 60.42 ± 5.41 minutes, and the mean resected tissue weight was 27.50 ± 8.06 grams. Complications occurred in 30% of patients within 90 days post-pTURP. A significant decrease in tPSA levels was observed after pTURP (p<0.05). Furthermore, the change in tPSA (delta tPSA) showed a linear and positive correlation with the weight of resected tissue.Conclusion: Palliative transurethral resection of the prostate in patients with advanced prostate cancer significantly reduces serum tPSA levels.